A guide to SQL - Pratt, Philip J.; Last, Mary Z. (Boston, Massachusetts : Course Technology Cengage Learning, 2009)
A Guide to SQL, 8th Edition continues to be the essential SQL reference. It builds on the success of previous editions by presenting basic SQL commands in the context of a running case in which a business uses SQL to manage orders, parts, customers, and sales reps. The book covers the fundamentals of SQL programming using straightforward instruction and extensive hands-on exercises. Continuing with its focus on students learning the basics regardless of the database environment chosen, this edition features examples from the latest databases: Oracle 11g, Access 2007, and MySQL. The eighth edition expands on the use of running case studies by adding a third running case to the extensive hands-on pedagogy at the end of every chapter.
Keywords: SQL (COMPUTER PROGRAM LANGUAGE)